Routledge philosophy guidebook to Kant on judgment - Wicks, Robert, 1954- (Routledge, 2007)
Kant's Critique of Judgment is one of the most important texts in the history of modern aesthetics. This GuideBook discusses the Third Critique section by section, and introduces and assesses:Kant's life and the background of the Critique of Judgmentthe ideas and text of the Critique of Judgment, including a critical explanation of Kant's theories of natural beautythe continuing relevance of Kant's work to contemporary philosophy and aesthetics. This GuideBook is an accessible introduction to a.